(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2017)
Makalah ini membincangkan isu berkenaan kualiti udara yang disebabkan oleh jerebu yang merentas sempadan negara Malaysia dan Singapura. Makalah ini menganalisis faktor dan impak jerebu dari pelbagai aspek, undang-undang domestik Malaysia dan Singapura, serta usaha negara serantau menyelesaikan masalah jerebu yang merentas sempadan menerusi perjanjian antara negara Association of Sourtheast Asian Nations (ASEAN), iaitu Asean Agreement on Transboundary Haze Pollution (AATHP). Hasil kajian mendapati Singapura lebih terkedepan menangani isu ini berbanding dengan negara ASEAN lain kerana Akta Pencemaran Jerebu Rentas Sempadan 2014 berjaya dikuatkuasakan di Singapura yang boleh dijadikan contoh oleh Malaysia. Kata kunci: jerebu, Malaysia, Singapura, perundangan, penguatkuasaan Abstract This article discusses issues related to air quality caused by transboundary haze pollution that seems to be an annual phenomenon that occurs particularly in the ASEAN region. Focus will be given to two countries namely Malaysia and Singapore which are clearly affected by this phenomenon. An analysis shall look into the factors and impacts of haze pollution from various aspects including a comparison study focusing on domestic laws of Malaysia and Singapore, and how the countries in the region seek solutions to the occurrence of transboundary haze through an agreement by ASEAN countries, that is the Asean Agreement on Transboundary Haze Pollution (AATHP). The study shows that Singapore is more advanced than the other ASEAN nations in handling this issue as it has been able to enforce the Transboundary Haze Pollution Act, a move which should serve as a model to Malaysia. Keywords: haze pollution, Malaysia, Singapore, law, enforcement